We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

#1**+1 **

This is the original equation:

\(96\pi = 24\pi+x(\frac{4}{3}\pi*27)\)

We want to solve for x here:

\(96\pi = 24\pi+x(\frac{4\pi}{3}*27)\) | First, evaluate what is in the parentheses. \(\frac{4\pi}{3}*27\) |

\(\frac{4\pi}{3}*27=\frac{4\pi}{3}*\frac{27}{1}=\frac{108\pi}{3}=36\pi\) | Reinsert this back into the original equation. |

\(96\pi=24\pi+36\pi x\) | Subtract \(24\pi\) on both sides of the equation. |

\({72\pi=36\pi x}\) | Divide both sides by the GCF of \(72\pi\) and \(36\pi x\). The pi will cancel out and the GCf of 72 and 36 is 36. Therefore, divide both sides by 36*pi. |

\(\frac{70\pi}{36\pi}=\frac{36\pi x}{36\pi}\) | Simplify both sides of the equation. |

\(2=x\) | x is already isolated, so we are done! |

We're done now! Yes!

TheXSquaredFactor Jul 31, 2017